Exploring the potential role of the advanced nurse practitioner within a care path for patients with chronic fatigue syndrome. (18th January 2017) - Ryckeghem, Hannah; Delesie, Liesbeth; Tobback, Els; Lievens, Stefaan; Vogelaers, Dirk; Mariman, An
Abstract: Aims: To explore the experiences and expectations of patients with chronic fatigue syndrome and general practitioners to develop the potential role of an advanced nurse practitioner at the diagnostic care path of abnormal fatigue developed for regional transmural implementation in the Belgian provinces of East and West Flanders. Background: Patients with chronic fatigue syndrome experience an incapacitating chronic fatigue that is present for at least 6 months. Since many uncertainties exist about the causes and progression of the disease, patients have to cope with disbelief and scepticism. Access to health care may be hampered, which could lead to inappropriate treatments and guidance. Design: Qualitative design. Methods: Individual semi‐structured interviews were conducted with patients with chronic fatigue syndrome and general practitioners in Belgium. Data were collected over 9 months in 2014‐2015. All interviews were audio recorded and transcribed for qualitative analysis using open explorative thematic coding. Results: Fifteen patients and 15 general practitioners were interviewed. Three themes were identified: mixed feelings with the diagnosis, lack of one central intermediator and insufficient coordination. Participants stressed the need for education, knowledge and an intermediator to provide relevant information at the right time and to build up a trust relationship. Conclusion: This qualitative exploration underscores some clear deficiencies in the guidance of patients suffering from chronic fatigue syndrome and abnormal fatigue. An advanced nurse practitioner as a central intermediator in the transmural care of these patients could promote interdisciplinary/multidisciplinary collaboration and effective communication, provide education and ensure a structured and coordinated approach.